Differential regulation of p62-ubiquitin conjugates in neurons versus astrocytes during cellular stress - David K. Sidibe; Erin M. Smith; Maeve L. Spivey; Maria C. Vogel; Sandra Maday (PLoS ONE, 2026)
Sequestosome 1/p62 (hereafter referred to as p62) is a multifunctional protein that orchestrates various cellular stress response pathways including autophagy, proteasome-mediated degradation, antioxidant defense, nutrient sensing, and inflammatory signaling. Mutations in distinct functional domains of p62 are linked with the neurodegenerative disease amyotrophic lateral sclerosis (ALS), underscoring its importance in neural cells. Neurons and astrocytes, two key cell types in the brain, perform distinct roles in brain physiology and thus encounter a unique landscape of cellular stress. However, how p62 is regulated in these cell types in response to various stress modalities remains largely unexplored. Several functions for p62 depend on its engagement with ubiquitinated substrates. Thus, we investigated how the regulation of p62-ubiquitin conjugates differs between neurons and astrocytes exposed to two stress modalities: lysosomal membrane damage and metabolic stress. Lysosomal damage triggered ubiquitin-dependent assembly of p62 puncta in both neurons and astrocytes. In contrast, nutrient deprivation elicited different responses between neurons and astrocytes. Neurons formed p62-ubiquitin structures more prominently and displayed a greater dependence on ubiquitin for p62 clustering. Together, these findings reveal cell-type-specific and stress-specific regulation of p62-ubiquitin conjugates, indicating that neurons and astrocytes can deploy distinct quality control strategies.